KEPEMIMPINAN KEPALA DAERAH DALAM PROSES PERCEPATAN PEMBANGUNAN GUNA MEWUJUDKAN MASYARAKAT MADANI - Putra, Firmasyah (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2017)
This paper describes how a successful district head is selected to continue the governance of the next five years. The focus of the study lies not on how successfully defend, seize or replace (officials) the old, but how efforts should be made after obtaining the political legitimacy of the people in order to accelerate development in order to realize the welfare of society. Succession is not just a process of change of power or election routine. This must be realized by an elite to show what commitment will be done when holding the power that has been mandated to him. Finally, it is wrapped with morals and ethics sourced from religious values ​​that will illuminate the behavior of the elite towards civil society.